2017
DOI: 10.1088/2043-6254/aa92b0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo tests of PLA/d-HAp nanocomposite

Abstract: The bioactivity of the PLA/d-HAp nanocomposite with 30 wt.% d-HAp was evaluated by in vitro tests and indicated that after 7 immersion days in SBF solution, PLA amorphous part was hydrolyzed and PLA crystal part was remained. The formation of apatite on the surface of the material was observed. The in vivo test results of PLA/d-HAp nanocomposite (70/30 wt/wt) on femur of dogs displayed that 3 months after grafting, the materials did not induce any osteitis, osteomyelitis or structural abnormalities. The histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The results showed that 3D-printed PLGA-PCL/HA microcomposite constructs promoted bone regeneration due to the formation of mineralized bone tissue and blood vessel. Very recently, Nguyen et al implanted solvent-cast PLA/30 wt% d-nHA nanocomposite into dog femurs [274]. Magnesium and zinc-doped nanohydroxyapatite (d-nHA) was used as the filler material.…”
Section: In Vivo Animal Modelsmentioning
confidence: 99%
“…The results showed that 3D-printed PLGA-PCL/HA microcomposite constructs promoted bone regeneration due to the formation of mineralized bone tissue and blood vessel. Very recently, Nguyen et al implanted solvent-cast PLA/30 wt% d-nHA nanocomposite into dog femurs [274]. Magnesium and zinc-doped nanohydroxyapatite (d-nHA) was used as the filler material.…”
Section: In Vivo Animal Modelsmentioning
confidence: 99%
“…Among the different synthesis routes, CVD has gained popularity for the production of graphene due to its economical and scalable approach along with its compatibility with current silicon technology. Many researchers have employed atmospheric/ambient pressure CVD to synthesize graphene using either Cu [11][12][13] or Ni [14][15][16][17] as a catalyst. The Ni-catalysed atmospheric pressure chemical vapour deposition (APCVD) synthesis of graphene generally employed either single or polycrystalline Ni thin films deposited on a suitable substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(lactic acid) (PLA)-biocompatible polymer often used because of its good biodegradability, high elastic modulus as well as the fact that the final degradation products of PLA are water and carbon dioxide, non-toxic or carcinogenic. Additionally, PLA has higher elastic modulus than natural cancellous bone [39]. Mechanical characteristics of composite coatings, e.g., elongation at break, substantially increased in hydroxyapatite nanorod network in the poly(lactic acid) [40].…”
mentioning
confidence: 99%